Males Are Capable of Long-Distance Dispersal in a Social Bee - Garcia Bulle Bueno, Francisco; Garcia Bulle Bueno, Bernardo; Buchmann, Gabriele; Heard, Tim; Latty, Tanya; Oldroyd, Benjamin P.; Hosoi, Anette E.; Gloag, Rosalyn (Frontiers in Ecology and Evolution, 2022)
Pollinator conservation is aided by knowledge of dispersal behaviour, which shapes gene flow and population structure. Stingless bees (Meliponini) are key pollinators in the global tropics and are vulnerable to inbreeding depression, yet female dispersal in these bees is restricted to a few hundred meters from parent nests due to their mode of colony founding. We assessed whether male dispersal in stingless bees offsets limited female dispersal, via study of Australia’s Tetragonula carbonaria. We placed colonies with virgin queens at varying distances apart (1-48 km), genotyped the males that gathered at mating aggregations outside each colony, and used pairwise sibship assignment to determine the distribution of likely brothers across aggregations. We then compared simulations of male dispersal to our observed distributions and found best-fit models when males dispersed an average of 1.3-3km, and maximum of 19km, from their natal nests. Mark-recapture of males supported these estimates, revealing that some males will fly 4.5 km in 48 hours. We conclude that males alleviate inbreeding in stingless bees by driving gene flow over distances up to 20-times the flight range of females. We also show that the genetic diversity of male aggregations can be used to estimate local stingless bee colony densities, thus allowing population monitoring of these important pollinators.